Regional Variation in End-of-life Care Just Before Death Among the Oldest Old in Japan: A Descriptive Study - Michi Sakai; Naohiro Mitsutake; Tomohide Iwao; Genta Kato; Shuzo Nishimura; Takeo Nakayama (Journal of Epidemiology)
Background: The use of life-sustaining treatment (LST) in the final stage of life is a major policy concern due to increased costs, while its intensity does not correlate with quality. Previous reports have shown declining trends in LST use in Japan. However, regional practice variations remain unclear. This study aims to describe regional variations in LST use before death among the oldest old in Japan. Methods: A descriptive study was conducted among patients aged 85 years or older who passed away between April 2013 and March 2014. The study utilized health insurance claims from Japan’s National Database (NDB) to examine the use of cardiopulmonary resuscitation (CPR), mechanical ventilation (MV), and admission to the acute care ward (ACW) in the last 7 days of life. Results: Among 224,391 patients, the proportion of patients receiving LST varied by region. CPR ranged from 8.6% (Chubu) to 12.9% (Shikoku), MV ranged from 7.1% (Chubu) to 12.3% (Shikoku), and admission to ACW ranged from 4.5% (Chubu) to 10.1% (Kyushu-Okinawa). The adjusted odds ratios (AOR) for regional variation compared with Kanto were as follows: CPR (in Shikoku, AOR 1.85; 95% confidence interval [CI], 1.73–1.98), MV (in Shikoku, AOR 1.75; 95% CI, 1.63–1.87), and ACW admission (in Kyushu-Okinawa, AOR 1.69; 95% CI, 1.52–1.88). Conclusion: The study presents descriptive information regarding regional differences in the utilization of LST for the oldest old in Japan. Further research is necessary to identify the factors that contribute to these variations and to address the challenge of improving the quality of end-of-life care.